Treatment patterns, risk factor control and functional capacity in patients with cardiovascular and chronic kidney disease in the cardiac rehabilitation setting: $hHeinz Völler, Anselm Gitt, Christina Jannowitz, Marthin Karoff, Barbara Karmann, David Pittrow, Rona Reibis and Steven Hildemann - Völler, Heinz; Gitt, Anselm Kai; Jannowitz, Christina; Karoff, Marthin; Karmann, Barbara; Pittrow, David; Reibis, Rona; Hildemann, Steven (European journal of preventive cardiology, 2014)
Background Chronic kidney disease (CKD) is a frequent comorbidity among elderly patients and those with cardiovascular disease. CKD carries prognostic relevance...
First published March 18, 2013
Gesehen am 16.09.2020